Single dose oral nefopam for acute postoperative pain in adults. - Kakkar, M; Derry, S; Moore, R; McQuay, H (2009)
BACKGROUND: Nefopam is a centrally-acting but non-opioid analgesic drug of the benzoxazocine chemical class, developed in the early 1970s. It is widely used, mainly in European countries, for the relief of moderate to severe pain as an alternative to opioid analgesic drugs, and used in rheumatic disease and other musculoskeletal disorders in the UK. This review sought to evaluate the efficacy and safety of oral nefopam in acute postoperative pain, using clinical studies of patients with established pain, and with outcomes measured primarily over 6 hours using standard methods. This type of study has been used for many decades to establish that drugs have analgesic properties. OBJECTIVES: To assess the efficacy of single dose oral nefopam in acute postoperative pain, and any associated adverse events. SEARCH STRATEGY: We searched CENTRAL (Issue 2, 2009), MEDLINE (1966 to May 2009); EMBASE via Ovid (1980 to May 2009); the Oxford Pain Relief Database (1950 to 1994); and reference lists of studies found. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled clinical trials of oral nefopam for relief of acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. The area under the "pain relief versus time" curve was used to derive the proportion of participants with nefopam and placebo experiencing least 50% pain relief over 4 to 6 hours, using validated equations. The number-needed-to-treat-to-benefit (NNT) was calculated using 95% confidence intervals (CIs). The proportion of participants using rescue analgesia over a specified time period, and time to use of rescue analgesia, were sought as additional measures of efficacy. Information on adverse events and withdrawals was also collected. MAIN RESULTS: No included studies were identified after examining in detail thirteen studies on oral nefopam in participants with established postoperative pain. AUTHORS' CONCLUSIONS: In the absence of evidence of efficacy for oral nefopam in acute postoperative pain, its use in this indication is not justified. Because trials clearly demonstrating analgesic efficacy in the most basic of acute pain studies are lacking, use in other indications should be evaluated carefully. Given the large number of available drugs of this and similar classes, there is no urgent research agenda.